The science of spin: targeted strategies to manufacture doubt with detrimental effects on environmental and public health - Rebecca F. Goldberg; Laura N. Vandenberg (BMC, 2021)
Abstract Background Numerous groups, such as the tobacco industry, have deliberately altered and misrepresented knowable facts and empirical evidence to promote an agenda, often for monetary benefit, with consequences for environmental and public health. Previous research has explored cases individually, but none have conducted an in-depth comparison between cases. The purpose of this study was to compile a comprehensive list of tactics used by disparate groups and provide a framework for identifying further instances of manufactured doubt. Methods We examined scholarly books, peer-reviewed articles, well-researched journalism pieces, and legal evidence related to five disparate industries and organizations selected for their destructive impacts on environmental and public health (tobacco, coal, and sugar industries, manufacturers of the pesticide Atrazine, and the Marshall Institute, an institute focused on climate change research, and other scientists from the era that associated with those in the Institute). These documents provided evidence for a list of tactics used to generate pro-industry spin and manufacture doubt about conferred harm. We then identified trends among sets of strategies that could explain their differential use or efficacy. Results We recognized 28 unique tactics used to manufacture doubt. Five of these tactics were used by all five organizations, suggesting that they are key features of manufactured doubt. The intended audience influences the strategy used to misinform, and logical fallacies contribute to their efficacy. Conclusions This list of tactics can be used by others to build a case that an industry or group is deliberately manipulating information associated with their actions or products. Improved scientific and rhetorical literacy could be used to render them less effective, depending on the audience targeted, and ultimately allow for the protection of both environmental health and public health more generally.